PID performance tuning methods for a robotic manipulator based on ISS - Choi, YJ; Chung, WK (WILEY, 2003)
This paper proposes performance tuning methods for a PID controller for a robotic manipulator. The design procedures of an inverse optimal PID control method employed to assure extended disturbance input-to-state stability (ISS) are suggested. The performance tuning methods for an inverse optimal PID control are derived from the performance limitation and the bounds of the state vector. Also, the effects of proportional and integral gains are considered in evaluating the performance tuning. Finally, we show the validity of the performance tuning methods through the experiment on a robotic manipulator.
Keywords: TO-STATE STABILITY; STABILIZATION